1984
DOI: 10.1002/jez.1402290114
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of an embryonic epithelium, the enveloping layer of the medaka (Oryzias latipes), a teleost

Abstract: The enveloping layer (EVL), a simple epithelium that forms the outer covering of the blastoderm of the teleost embryo, contracted in situ when it was exposed to the calcium ionophore A23187. This contraction was inhibited by cytochalasin D and occurred in a Ca2+-free medium. When the EVL was detached from the rest of the embryo, it contracted into a tight ball. Detached EVLs contracted fully in Na+-, K+-, SO;--, M?'-, or glucose-free medium but only partially in medium containing less than 10 pM free Ca2+. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The rhythmic calcium waves could be related to the propagating calcium waves that accompany the rhythmic contraction of the stellate layer of medaka. (53)(54)(55) In the case of zebrafish, however, the pacemaker region generating these waves becomes established in the embryonic shield at the dorsal midline of the blastoderm margin, whereas in medaka the equivalent region is located on the opposite side of the embryo. (54) In addition, the period when the rhythmic waves occur in zebrafish overlaps with comparable stages of Xenopus development in which repeated calcium pulses and, possibly, waves were reported from dissociated neural plate cells.…”
Section: Calcium Signalling During the Blastula Periodmentioning
confidence: 97%
“…The rhythmic calcium waves could be related to the propagating calcium waves that accompany the rhythmic contraction of the stellate layer of medaka. (53)(54)(55) In the case of zebrafish, however, the pacemaker region generating these waves becomes established in the embryonic shield at the dorsal midline of the blastoderm margin, whereas in medaka the equivalent region is located on the opposite side of the embryo. (54) In addition, the period when the rhythmic waves occur in zebrafish overlaps with comparable stages of Xenopus development in which repeated calcium pulses and, possibly, waves were reported from dissociated neural plate cells.…”
Section: Calcium Signalling During the Blastula Periodmentioning
confidence: 97%
“…The importance of external Ca 2+ ions for cell-cell adhesion during embryonic development has been emphasized frequently in various animals (Herbst, 1900(Herbst, , 1904Yanagimachi, 1957;Takeichi & Okada, 1972;LeBlanc & Brick, 1981;Hyafil et al, 1981;Fluck et al, 1984). It is probable that the separation of blastomeres in 14·3% SRS is due to the absence of adhesion molecules on the cell surface and is related to relatively low contents of Ca 2+ ions in this solution (3·2 m).…”
Section: Formation Of Enveloping Layer In Isotonic Salt Solutions Witmentioning
confidence: 99%
“…A thin layer of stellate-like cells beneath the EVL is responsible for the contractile movements (Cope et al, 1990). The contraction waves depend on extracellular calcium (Fluck et al, 1984) and can be inhibited by inorganic calcium antagonists (Fluck et al, 1984;Sguigna et al, 1988) or stimulated by the calcium ionophore A23187 (Fluck et al, 1984). More recently it was found that contraction waves are preceded by intercellular Ca 2þ waves and intracellular Ca 2þ oscillations within the stellate cell layer, indicating a role for gap junctional communication (Fluck et al, 1991;Simon and Cooper, 1995).…”
Section: Introductionmentioning
confidence: 98%